Pengaruh Kepemimpinan Transformasional, Budaya Organisasi, dan Teknologi Informasi Terhadap Kinerja Karyawan (Studi pada Karyawan Pabrik Gula Wonolangan Kabupaten Probolinggo) - Rahman, Muhammad Taufiqur; Widarko, Agus; Ramadhan, Tri Sugiarti (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine and analyze the influence of transformational leadership, organizational culture, and information technology on employee performance in the study of Wonolangan Sugar Factory employees in Probolinggo Regency. This type of research uses quantitative methods. The population is Wonolangan Sugar Factory employees with a sample of 80 respondents, and applies sampling, namely the saturated sample method. The data sources obtained come from distributing questionnaires and data processing using SPSS version 25.0 analysis media. The results of the analysis and testing show simultaneously and partially that Transformational Leadership (X1), Organizational Culture (X2), and Information Technology (X3) have a positive effect on Employee Performance (Y).  Keywords: Transformational Leadership, Organizational Culture, Information Technology, Employee Performance